Analysis of the Effect of Government Spending and Human Development Index on Economic Growth in Indonesia 2021 – 2022 - Saragih, Erick Jhon Clever; Azansyah (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study was to determine the effect of government spending and Human Development Index on economic growth in Indonesia. This study uses panel data with Fixed Effect Model approach. In this research, the type and source of data used is secondary data from the Central Bureau of Statistics (BPS). The data used in this study is a combination of cross section data and time series data of 34 provinces in Indonesia from 2021-2022 (penel data). The variables used in this study are economic growth (Y) in Percent units, government spending (X1) in logarithmic rupiah units and Human Development Index (X2) in Percent units. The method used in this study is the method of analysis of panel data (pooled data) as a tool to process data using eviews 9. It was found that government spending and Human Development Index have a positive influence on economic growth.